Determinants of Palestine Takaful Insurance Companies Profitability - Qubbaja, Adnan (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2025)
The purpose of this paper is to investigate the factors that determine the profitability of insurance Takaful companies in Palestine; the study population consisted of insurance Companies listed at the Palestine Stock Exchange during the period (2018-2022). We collected the data from the reports of two Takaful Insurance companies for the period 2018-2022. The researcher used the multiple regression econometrics models. The study shows that profitability was usually expressed as a function of internal and external determinants. Results of the study confirm that liquidity, Leverage are the factors that significantly affect the profitability of Takaful insurance companies in Palestine. Size, Leverage, Tangibility of assets, Growth rate of GDP, and Inflation Rate affect the profitability positively, but liquidity has a negative effect on profitability. Size, Tangibility of assets, Growth rate of GDP, and Inflation Rate have insignificant impacts on ROE and ROA. The key implications of these findings suggest that Palestinian insurance companies should consider diversifying their portfolios beyond motor insurance to improve profitability. Additionally, it is recommended that companies explore merger opportunities to increase operational scale and achieve economies of scale. Furthermore, maintaining a high level of liquidity is crucial, as it allows companies to effectively secure bids and promptly settle claims, which not only enhances their reputation but also positively impacts profitability.